The Architecture of Innovation: Tracking Face-to-Face Interactions with Ubicomp Technologies - Brown, Chlöe; Efstratiou, Christos; Leontiadis, Ilias; Quercia, Daniele; Mascolo, Cecilia; Scott, James; Key, Peter (Proceedings of UbiComp 2014, 2014)
The layouts of the buildings we live in shape our everyday lives. In office environments, building spaces affect employees’ communication, which is crucial for productivity and innovation. However, accurate measurement of how spatial layouts affect interactions is a major challenge and traditional techniques may not give an objective view. We measure the impact of building spaces on social interactions using wearable sensing devices. We study a single organization that moved between two different buildings, affording a unique opportunity to examine how space alone can affect interactions. The analysis is based on two large scale deployments of wireless sensing technologies: short-range, lightweight RFID tags capable of detecting face-to-face interactions. We analyze the traces to study the impact of the building change on social behavior, which represents a first example of using ubiquitous sensing technology to study how the physical design of two workplaces combines with organizational structure to shape contact patterns.